DNA Demethylation Upregulated Nrf2 Expression in Alzheimer’s Disease Cellular Model - Cao, Huimin; Wang, Li; Chen, Beibei; Zheng, Peng; He, Yi; Ding, Yubin; Deng, Yushuang; Lu, Xi; Guo, Xiuming; Zhang, Yuping; Li, Yu; Yu, Gang (Frontiers in Aging Neuroscience, 2016)
Nuclear factor erythroid 2-related factor 2 (Nrf2) is an important transcription factor in the defense against oxidative stress. Cumulative evidence has shown that oxidative stress plays a key role in the pathogenesis of Alzheimer's disease (AD). Previous animal and clinical studies had observed decreased expression of Nrf2 in AD. However, the underlying regulation mechanisms of Nrf2 in AD remain unclear. Here, we used the DNA methyltransferases (Dnmts) inhibitor 5-aza-2′-deoxycytidine (5-Aza) to test whether Nrf2 expression was regulated by methylation in N2a cells characterizing by expressing human Swedish mutant amyloid precursor protein (N2a/APPswe). We found 5-Aza treatment increased Nrf2 at both mRNA and protein levels via down-regulating the expression of Dnmts and DNA demethylation. In addition, 5-Aza mediated upregulation of Nrf2 expression was concomitant with increased nuclear translocation of Nrf2 and higher expression of Nrf2 downstream target gene NAD(P)H:quinone oxidoreductas (NQO1). Our study showed that DNA demethylation promoted the Nrf2 cell signaling pathway, which may enhance the antioxidant system against AD development.